Pharmacological attributes of Bacopa monnieri extract: Current updates and clinical manifestation - Fatima, Urooj; Roy, Sonam; Ahmad, Shahnawaz; Ali, Sabeeha; Elkady, Wafaa M.; Khan, Ilyas; Alsaffar, Rana M.; Adnan, Mohd; Islam, Asimul; Hassan, Md. Imtaiyaz (Frontiers in Nutrition, 2022)
Bacopa monnieri has been used for centuries in Ayurvedic medicine, alone or in combination with other herbs, as a memory and learning enhancer, sedative, and anti-epileptic. This review aimed to highlight the health benefits of B. monnieri extracts (BME), focusing on anti-cancer and neurodegenerative diseases. We examined the clinical studies on phytochemistry and pharmaco-logical application of BME. We further highlighted the mechanism of action of these extracts in varying types of cancer and their therapeutic implications. In addition, we investigated the un-derlying molecular mechanism in therapeutic interventions, toxicities, safety concerns and synergistic potential in cognition and neuroprotection. Overall, this review provides deeper in-sights into the therapeutic implications of Brahmi as a lead formulation for treating neurological disorders and exerting cognitive-enhancing effects.